Linguistic Fundamentalism - Ruszkowski, Marek (Respectus Philologicus, 2016)
The term fundamentalism was first used in 1910 in the United States with reference to the American Protestants who had literal understanding of the Bible and rejected the theory of evolution. The term fundamentalism can be as well used to denote extreme orthodox attitudes to language, which are characterised by the irrational, radical, strictly emotional approach to linguistic phenomena. Such phenomena are not analysed sine ira et studio, and the authors of normative verdicts have insufficient knowledge of linguistics. It is about the purist attitudes (nationalist, orthodox, egocentric, elitist), perfectionism and applications of logics to the language. Even though emotional and very subjective attitudes to the language phenomena can be partly justified if they are represented by the average users of the Polish language, it is hard to find justification of it when it comes to linguists. Each science (including linguistics) should strive to rationally recognise and describe the reality, and the linguists’ objective is to make efforts to find the judgements about language which are logically strict and methodologically justified.